(untitled) (Metallurgy and Foundry Engineering, 2005)
It was attempted in this work to study the applicability of Butler approach to the metal oxide solutions. First of all, the authors tried to determine the impact of the thermodynamic activity coefficients of the components of the bulk phase on the surface tension. The activity coefficients series expansions reported by Ban-ya and one of the authors of this work were used. The model equations were solved by means of a Newton regression method, which allowed to calculate the components contents in the surface phase. Those contents were subsequently substituted into the modified Butler master equation, which gave desired final surface tensions estimates for the considered oxide binaries. The computations were done for liquid MnO-SiO2 system (at 1843 K and 1990 K) and subsequently for MnO-AI2O3 (at 2058 K) and MnO-CaO (at 2473 K) systems. For MnO-SiO2 system at 1843 K, the obtained results could be compared to the experimental ones and a fairly good agreement was found. For MnO-Al2O3 and MnO-CaO systems, unfortunately, there is no experimentally measured surface tension data, therefore it was not possible to make any comparison. Nevertheless, the model may be quite useful for the surface tension estimates for the systems, which have not been yet investigated and such model calculations like presented in this work may provide acceptable predictions.